The Evaluation of Learning Assessment in Higher Education: from the perception of students to the ideal evaluation - Pereira, Orlando Petiz; Costa, Carlos Arriaga (Advances in Social Sciences Research Journal, 2018)
Pedagogical practices in higher education have been experiencing important changes, most of which are in line with the principles of the Bologna Reform. The new learning methodologies seem to have prompted different procedures in the evaluation process. The programs were redesigned to respond to an environment, which is ever more competitive. As a result, the ideas of excellence and efficiency embody the objectives of teaching and the result of evaluation of students came to be regarded as a fundamental tool in the selection process and visibility. This study aims at analyzing in-depth the experiences of evaluation of undergraduate students (1st cycle) and graduate students (2nd cycle) in two different periods: the first covering for the years of 2008 and 2009 and the second for 2016 and 2017. These periods are two important milestones in the implementation of the Bologna Declaration because they mirror the beginning and the progress of the Bologna Reform. This study does also seek to identify the reasons, which enshrine the perceptions of evaluation experiences and the meaning of the ideal model of evaluation. Although the sensitivity/uneasiness does persist in the evaluation perception, this study's results seem to be rather relevant.